EKSPLORASI ETNOMATEMATIKA DALAM TRADISI BEDURUK SUKU DAYAK DESA KABUPATEN SINTANG - Gabrielle Ernesto; Agung Hartoyo; Dian Ahmad (Universitas Tanjungpura, 2022)
This research aims to explore mathematical activities andmathematical concepts contained in the Beduruk tradition carried outby the Dayak Desa tribe who live in Sintang Regency. The researchmethods used in this study are qualitative with an ethnographicapproach. Data is collected using semi-structured interview methods,passive participatory observation, and documentation. The subject inthis study is the Dayak Desa tribe participants who still carry out thetradition of Beduruk in Medang, Mangat Baru, Dedai District, SintangRegency. Based on Miles and Huberman's analytical methods, themathematical activity contained in the Beduruk tradition is tocalculate, measure, design, playing, and explain. While themathematical concepts contained in the Beduruk tradition are sets,direct proportion and inverse proportion, plane circumference,measurements, probability, volumes, and lines.